The global prevalence of Toxocara spp. in pediatrics: a systematic review and meta-analysis - Behnam Abedi; Mehran Akbari; Sahar KhodaShenas; Alireza Tabibzadeh; Ali Abedi; Reza Ghasemikhah; Marzieh Soheili; Shnoo Bayazidi; Yousef Moradi (The Korean Pediatric Society, 2021)
Background Toxocariasis is a zoonotic parasitic disease caused by Toxocara canis and Toxocara cati in humans. Various types of T. canis are important. Purpose The current study aimed to investigate the prevalence of Toxocara spp. in pediatrics in the context of a systematic review and meta-analysis. Methods The MEDLINE (PubMed), Web of Sciences, Embase, Google Scholar, Scopus, and Cumulative Index of Nursing and Allied Health databases were searched to identify peer-reviewed studies published between January 2000 and December 2019 that report the prevalence of Toxocara spp. in pediatrics. The evaluation of articles based on the inclusion and exclusion criteria was performed by 2 researchers individually. Results The results of 31 relevant studies indicated that the prevalence of Toxocara spp. was 3%-79% in 10,676 cases. The pooled estimate of global prevalence of Toxocara spp. in pediatrics was 30 (95% confidence interval, 22%-37%; I2=99.11%; P=0.00). The prevalence was higher in Asian populations than in European, American, and African populations. Conclusion Health policymakers should be more attentive to future research and approaches to Toxocara spp. and other zoonotic diseases to improve culture and identify socioeconomically important factors.